FAKTOR RISIKO PENYAKIT KANKER PAYUDARA DI WILAYAH ASIA (DENGAN PENDEKATAN STUDI META ANALISIS) - Alfita Dewi (Ensiklopedia of Journal, 2020)
Breast cancer is the most common cancer in women. With an estimated 1.7 million cases and 521,900 deaths in 2012. Of these estimates, 39% in Asia, 29% in Europe, 15% in America, 8% in Africa, and 1.1% in Australia.This study aims to see risk factors for breast cancer incidence in the Asian region. This research is quantitative with the design of meta-analysis study of the research with the design of case-control and cohort studies. Search through ProQuest, PubMed, Biomed Central, and EBSCO Host databases. The data is processed using RevMan 5.3 application. The results showed a significant correlation to family history of cancer (OR: 1.57 95%CI 1.22-2.02), age of menopause ≥50 years (OR: 1.20 95%CI 1.04-1,39), and the first delivery age was ≥30 years (OR: 1.54 95%CI 1.18-2.02) with breast cancer in the Asian Region. While age (OR: 1,11 95%CI 1.00-1.24), age at menarche